ONLINE PURCHASE THROUGH MOTIVATION AND SATISFACTION ON REPEAT INTENTION: THE CONCEPT OF SELF DETERMINATION THEORY - Yuliatin Azizah; Saiful Amin (ABM: International Journal of Administration, Business and Management, 2023)
Online businesses are able to access a broad and global market, without being limited by geographical boundaries. Indonesian society has a large number of online users. This opens up huge online market opportunities. Online buyers who tend to change places of purchase are interested in doing research. In accordance with this, research was carried out to optimize online purchases through motivation within the framework of the self-determination theory concept and adding one variable, namely satisfaction. The method used is quantitative research with survey methods and is an equation model structure with the measurement tool WrapPLS 7.0. The research results show that optimizing purchases by looking at motivation uses self-determination theory consisting of external regulation, introjected regulation, identified regulation, integration regulation and intrinsic regulation. The model becomes better with the mediation of consumer satisfaction.